Understanding what it means to be socially included for people with a lived experience of mental illness. (August 2019) - Filia, Kate; Jackson, Henry; Cotton, Sue; Killackey, Eoin
Aims: Social inclusion is increasingly understood to have positive and beneficial implications for the mental health outcomes of people with severe mental illness. The concept is plagued by definitional inconsistencies and a lack of consensus regarding what it means to be socially included, in particular for groups most vulnerable to social exclusion, such as people with mental illness. The aim of this study was to obtain a consensus regarding the key contributors to social inclusion from the perspective of people with and without a lived experience of mental illness (consumers of mental health services, carers, and general community members). Methods: Delphi methodology was employed to reach consensus agreement. The Delphi questionnaire was based on a previous review of the literature and consisted of 147 items categorized into 13 domains. It was presented to participants over three rounds. Participants ( N   =  104) were recruited into three groups (32 consumers, 32 carers of people with a mental illness, and 40 members of the general community – neither consumers nor carers). Retention of participants from Round 1 to Round 3 was 79.8%. Results: Similarities and differences were observed between the groups. A number of items were very strongly endorsed as key contributors to social inclusion, relating to social participation, social supports, housing, neighbourhood, community involvement, employment and education, health and well-being and service utilization. Conclusion: Findings supported previous work, indicating the importance of having a strong sense of connection with others as well as the importance of safe and stable housing, support services and personal motivation and hope. We obtained a well-rounded perspective among groups regarding the key contributors to social inclusion, with a particular relevance to people living with mental illness. This perspective has significant clinical and research utility.